Gene expression profiling of selenophosphate synthetase 2 knockdown in Drosophila melanogaster. Issue 3 (29th January 2016) - Li, Gaopeng; Liu, Liying; Li, Ping; Chen, Luonan; Song, Haiyun; Zhang, Yan
Abstract : Transcriptome analysis of SPS2 knockdown suggests a new relationship between selenium utilization and fundamental cellular processes as well as diseases. Abstract : Selenium (Se) is an important trace element for many organisms and is incorporated into selenoproteins as selenocysteine (Sec). In eukaryotes, selenophosphate synthetase SPS2 is essential for Sec biosynthesis. In recent years, genetic disruptions of both Sec biosynthesis genes and selenoprotein genes have been investigated in different animal models, which provide important clues for understanding the Se metabolism and function in these organisms. However, a systematic study on the knockdown of SPS2 has not been performed in vivo . Herein, we conducted microarray experiments to study the transcriptome of fruit flies with knockdown of SPS2 in larval and adult stages. Several hundred differentially expressed genes were identified in each stage. In spite that the expression levels of other Sec biosynthesis genes and selenoprotein genes were not significantly changed, it is possible that selenoprotein translation might be reduced without impacting the mRNA level. Functional enrichment and network-based analyses revealed that although different sets of differentially expressed genes were obtained in each stage, they were both significantly enriched in the carbohydrate metabolism and redox processes. Furthermore, protein–protein interaction (PPI)-based network clustering analysis implied that several hub genes detected in the top modules, such as Nimrod C1 and regucalcin, could be considered as key regulators that are responsible for the complex responses caused by SPS2 knockdown. Overall, our data provide new insights into the relationship between Se utilization and several fundamental cellular processes as well as diseases.